Infecções estafilocócicas em cães: prevalência, resistência antibacteriana, fatores de risco e de virulência - Martins, Christina Resende (2020)
Despite being considered a bacteria that is part of the natural microbiota of dogs' skin, S. pseudintermedius has been associated with infections in skin and delicate tissues in dogs, as well as some cases of infections in humans. The thesis was divided into three chapters, the first referring to the general considerations of topics covered in the other chapters. The second chapter aimed to evaluate the resistance profile to a panel of more than 30 antimicrobials, with bacteria isolated from 698 clinical samples of dogs between the years 2016 and 2018. For the evaluation, results from diffusion tests on discs performed in a private laboratory between the years 2016 to 2018 were used. The analysis of the results determined the etiological agents mostly involved in infections and the temporal evolution of antibacterial resistance. The third chapter aimed to evaluate the presence of S. pseudintermedius in clinical samples taken from dogs’ skins and ears, and the nostrils of their guardians. As well as evaluate the presence of resistance genes mecA, mecA1 and mecA2, which confer resistance to β-lactam antimicrobials, gene msr responsible for resistance to macrolides, and virulence genes FnbB (cell invasion) and PVL (leukotoxin), using PCR technique. The in vitro performance of antimicrobials oxacillin, cefovecin and gentamicin was determined by the methods of disk diffusion and minimum inhibitory concentration - MIC. It also determined the association of factors related to the animal's lifestyle with infection with S. pseudintermedius, an association between the presence of genes and antimicrobial resistance and the tests.